The Role of Marketing in the Football Business - Khoshtaria, Tornike (Management and Administration Journal, 2023)
The aim of this study is to investigate the importance of marketing in the football business. In order to accomplish the task the study mainly concentrated its research efforts on customers (fans), to find out whether or not customers are satisfied, and whether they would therefore stay loyal to their clubs for a long time. Additionally, the paper is concerned with the product life cycle of football and the role of marketing in its extension. Secondary data has been collected and critically analysed in order to see whether or not theoretical measurements lack the ability to be implemented correctly in the practical world of the football business.